CORRELATION ANALYSIS: Are Religious Scavengers More Motivated? - Karim, Ibnu Nur (AKADEMIK: Jurnal Mahasiswa Humanis, 2021)
A scavenger community is a group of people who pick up used goods such as garbage for recycling. , or sorting out items that are considered useful from waste, both in landfills and outside. There are two types of scavengers namely freelance scavengers, who work as self-employed, and scavengers who depend on a dealer who lends money to them and deducts the loan money when buying goods from scavengers. The research method used is descriptive method, the approach used is quantitative. The formula used to measure this research is the Pearson Product Moment correlation formula. Sampling was done by using a simple random sample. Based on the results of the correlation analysis, it was stated that there was a significant relationship between religious development and the work motivation of scavengers.